Precarity in the lives of contract teachers: A qualitative study from Odisha, India - Apat, Biswajit; Swain, Pranaya (Frontiers in Education, 2023)
School enrollment rates in developing countries have increased substantially over the past few decades. However, due largely to budget constraints, hiring contract teachers has become an ad hoc, yet a popular solution to teacher shortages in Asia, Africa, and Latin America. Studies concerning contract teachers have primarily focused on their performance, efficiency, and cost-effectiveness. In light of the literature on precarity associated with contractual employment, this article seeks to explore how contractual employment affects teachers in India. The study analyzes narrative data obtained through semistructured interviews with seventeen contract teachers employed in government-run schools in Odisha, a state in eastern India. According to thematic analysis of the data, participants experience precarity in six dimensions: prioritisation of non-teaching work over teaching, financial hardships, sense of inferiority, anxiety about transfer, experiences of discrimination, and desire for course correction. We argue that these six dimensions contribute to the demoralization and disempowerment of teachers. We also explore possible explanations for why Odisha continues to employ contract teachers despite criticism. It is recommended that policymakers be sensitized to the plight of contract teachers and reconsider the policy of contractual employment.